Makna Simbolik Tradisi Jawa Munggahna Kuda-Kuda pada Masyarakat Kabupaten Malang - Ribowo, Erik Prastiyo; Purwaningsih, Susi; Iswatiningsih, Daroe (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
The procession of installing the roof frame of a house, which is termed as Munggahna Kuda-kuda in Javanese society, is carried out with a procession. This is done as a tradition that has been passed down from generation to generation and is believed to prevent the owner of the house from bad luck that might happen in the future. The purpose of this research is 1) to describe the procession of Munggahna Kuda-kuda Malang Regency, 2) the symbolic meaning of offerings in Munggahna Kuda-kuda Malang Regency. This type of research is descriptive qualitative with a semiotic approach in studying the culture of the local community. The sampling technique in this study used nonprobability sampling with purposive sampling. Research data and data sources in the form of the Mungahna Kuda-kuda tradition in Javanese society, especially in Malang Regency. The data collection technique in this research is by conducting interviews with sources of literature study on manuscripts. The results of this study are in the form of a procession in this tradition starting with determining the naga tahun or cardinal direction in accordance with the month in the Javanese calendar. second, determining the naga dina or good day in accordance with community beliefs. Third, a joint prayer event attended by workers and local residents with a dish consisting of sega golong and jenang sengkolo or glutinous rice porridge consisting of two colors, red and white. The fourth is the process of installing the roof of the house which is accompanied by the installation of offerings. Each offering consists of rice, corn, sugar cane, bananas, a red and white flag, and a set of clothes (sewek, shirt, and veil). Each symbol has its own meaning. The determination of the direction of the wind, the day, and the symbols in the offerings and selamatan dishes have a good purpose, namely as a manifestation of gratitude and prayers for safety to the Almighty in accordance with community beliefs.